From relief to risks: a comprehensive review of medical cannabis - Lokhande, Nidhi; Mokal, Aditya; Deshmukh, Namita; Borkar, Avinash; Patil, Suvarna (International Journal Of Community Medicine And Public Health, 2025)
Cannabis has been used for medicinal purposes for thousands of years, with a resurgence in modern medical applications sparking significant research and regulatory discussions. This review explores the medical benefits, risks, mechanisms of action, and legal considerations of cannabis use. Cannabis-based treatments have shown efficacy in managing multiple conditions, including chronic pain, multiple sclerosis, psychiatric disorders, chemotherapy-induced nausea, epilepsy, and neurodegenerative diseases. Despite its therapeutic potential, cannabis use carries short- and long-term risks, including cognitive impairment, cardiovascular issues, dependency, and adverse mental health effects. The variability in cannabis products, dosing, and regulation raises concerns regarding safety and quality control. Additionally, ethical dilemmas exist in prescribing unstandardized cannabis-based therapies. Legalization trends across various regions continue to shape the accessibility and acceptance of medical cannabis, though significant research gaps remain. Future studies are required to further validate its efficacy, optimize dosing strategies, and mitigate potential health risks. This review provides a comprehensive overview of current evidence, highlighting both the promise and challenges associated with medical cannabis.